PERSEPSI MENGENAI RISIKO DAN KONSUMSI MINUMAN BERPEMANIS PADA REMAJA - Purnama, Maria Meidiary; Sutiari, Ni Ketut (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025, 2025)
ABSTRACT The prevalence of sweetened beverage consumption among adolescents is notably high in Indonesia, carrying a potential risk for diabetes mellitus. Based on the 2018 National Health and Nutrition Examination Survey, the consumption of sweetened beverages appears to be relatively elevated, with 63% among adolescents aged 12-19 years and 51% among young adults aged 20-39 years. However, the underlying factors influencing this trend remain unidentified. Hence, this study aims to investigate the perceptions regarding risks and patterns of sweetened beverage consumption among adolescents in West Denpasar. This research utilizes a descriptive cross-sectional design and employs purposive random sampling through a questionnaire-based survey. The research findings indicate that adolescents with positive perceptions in terms of perceived benefits and satisfaction amounted to 59 adolescents (57.8%), while those with negative perceptions regarding their understanding of health risks related to sweetened beverages were 43 adolescents (42.2%). All respondents have consumed one or more packaged and non-packaged sweetened beverages. The majority of respondents very rarely or at a minimum once a month consume packaged and non-packaged sweetened beverages. Nonetheless, respondents exhibit variations in their habits of consuming sweetened beverages such as coffee, tea, sports drinks, fruit drinks, and milk. Consequently, it is recommended that the government intensify efforts in enhancing labeling and nutritional information for sweetened beverages. Collaborative initiatives with educational institutions should also be pursued to incorporate comprehensive nutritional education. This concerted approach aims to equip adolescents with the skills to discern and interpret nutritional labels, enabling them to make informed and health-conscious choices regarding their dietary intake. Keywords: Sweetened Beverages, Perception,  Adolescents